Концентуальні засади енергоефективного керування випічкою хліба з використанням інтелектуальних технологій - Козирський, В. В.; Момотюк, В .В. (Energy and Automation, 2017)
Conceptual framework of energy efficient baking bread CONTROL WITH INTELLIGENT TECHNOLOGY V. Kozyrcky, V. Momotyuk Annotation. Reviewed bread production processes in modern factories in terms of energy efficiency and quality. The generalized structural scheme of electro-technological complex of bakery production. Based on a systematic analysis of the conclusions about continuity and complexity processes; background of installed control systems; summarizes the shortcomings of existing analogues. The block diagram of energy efficient control systems using artificial intelligence technologies. Key words: bakery production, energy efficiency, control system, neural network, range, waste heat